Sintesis dan Kajian Docking Molekular Senyawa 2’-Hidroksicalkon dan Flavonol Tersubstitusi Dimetoksi sebagai Inhibitor Kompleks NS2B-NS3 Serine Protease pada Virus Dengue-2 (DENV-2) - Ikhtiarudin, Ihsan; Frimayanti, Neni; Hendra, Rudi; Teruna, Hilwan Yuda; Rahim, Fatma; Mora, Enda; Septama, Abdi Wira (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Exploration of the potential compounds as dengue antivirals is one of the efforts that must be considered, because no specific therapy has been found with antiviral drugs that is effective in treating dengue hemorrhagic fever (DHF) patients. The aim of this study is to synthesize and explore the potential of the (E)-3-(2,5-dimethoxyphenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one (compound 1) and 2-(2,5-dimethoxyphenyl)-3-hydroxy-4H-chromen-4-one (compound 2) as inhibitors of NS2B-NS3 serine protease complex of DENV-2. Synthesis of compounds 1 and 2 was carried out by stirring using a magnetic stirrer. The structures of the two synthesized compounds have been confirmed through UV-Vis, FT-IR and 1H NMR spectroscopic analyses. Molecular docking was performed using NS2B-NS3 complex (PDB ID: 2FOM) as a receptor. Compounds 1 and 2 were obtained in 21.11% and 66.84% yield, respectively. Based on the molecular docking studies, compounds 2 exhibited more negative binding free energy than compound 1 and panduratin A as a reference inhibitor. Compound 2 was observed to bind to the catalytic triad of NS2B-NS3 complex (His51, Asp75, Ser135) and form hydrogen bond with Gly153. Based on the results, it can be concluded that compounds 1 and 2 can be synthesized by stirring method and the compound 2 showed good potency to be developed as inhibitors of the NS2B-NS3 serine protease complex of DENV-2.